Study of level of malondialdehyde and total antioxidant capacity (TAC) in human lens epithelial cells of diabetic and senile cataract patients - Kranti Santosh Sorte Gawali; Avinash Namdeo Jadhao (Advances in Medical, Pharmaceutical and Dental Research)
Background: Oxidative stress is a condition where the balance between the production and elimination of reactive oxygen species (ROS) is disturbed. ROS can cause damage to various biomolecules, including DNA. DNA damage can impair the function and survival of cells, and may contribute to the development of cataracts. Several experimental studies have shown that oxidative stress is involved in cataract formation by inducing DNA damage in lens cells.. ROS are created in diabetic tissues by glucose autoxidation as well as non-enzymatic protein glycation. ROS is thought to play a significant role in the development of microvascular problems in diabetic individuals Objectives: To measure the levels of total antioxidant capacity and Malondialdehyde (MDA) in diabetic and nondiabetic senile cataract patients and comparison between them. Patients and methods: Thirty Senile cataract cases and 30 diabetic cataract cases aged 50-80 years who were brought to the ophthalmology ward of Acharya Vinoba Bhave Rural Hospital  for cataract surgery were used for TAC assay and malondialdehyde determination in lens epithelial cells of diabetic and senile cataract. Results: TAC was decreased in human lens epithelial cells of diabetic and senile cataract group. TAC is more reduced in diabetic than senile cataract group, it is not statistically significant. higher levels of MDA  in human lens epithelial of Diabetic cataract patients as compared to senile cataract patients. Conclusion: The conclusion in the present study diabetes may cause ocular complications by affecting the lens of the eye. This is because diabetic patients have lower levels of TAC and higher levels of Malondialdehyde in their lens than senile cataract patients. These factors may contribute to pathogenesis of diabetic cataract.   Received: 23 June 2023 Accepted: 09 August 2023 Published: 25 August 2023